Contest and co-option : the struggle for schooling in the African independent churches of the Cape Colony - Paterson, Andrew Neil Macleod (School of Education, 2014)
The establishment of schools by independent African churches reflected changes in the complex amalgam of forces that constituted the social fabric of ordinary black people in the Cape Colony between 1895 and 1920. These churches and schools were in part a creative response to discriminatory mission church politics, a general decline in black economic fortunes, and changes in the nature of black political mobilisation. However, the advent of independent church schools did not merely reflect an ideological preoccupation with colonial dominance. They were initiated to meet a range of educational needs articulated by numbers of urban and rural blacks. This demand for educational opportunities signalled the progressive incorporation of formal western education within the social lives of many black people in the Cape. Moreover, in this crucial period, schooling in the Cape Colony was being segregated as the principal element in a programme introduced by the Education Department to curtail spending on black education and to boost subsidies to white education. Blacks were therefore limited to mission schools which were inadequate and characterised by a lack of community control. Consequently, independent church communities were preoccupied with the politics of access and control in the schools. Within the gradually unfolding Cape education 'system', missionary control was tenuous in the uncoordinated rural mission outstation schools. There, independent school communities seized the opportunity to pursue their own objectives. However, each group of independent church schools was in some way conditioned by the ability of colonial representatives to dictate the political, financial and administrative terms of their existence. In this respect, the independent school communities negotiated the ambiguous terrain between the poles of contest and co-option. The more successful initiatives managed to solicit Education Department funding while minimising interference from white intermediaries, school inspectors and mission church agents. Nevertheless, government recognition and funding mechanisms facilitated the eventual capture of the independent schools within the colonial education system. Thus, this work reflects as much on the emergence of the Cape education system, as on the question of resistance to mission control. The independent church schools were not solely characterised by contest with missionaries or the government education authorities. African Christian school communities in rural locations in the Eastern Cape were divided internally by school, ethnic and church allegiances which affected their access to scarce commodities such as education and land. Competition over access to schooling therefore gave rise to serious conflict between African independent church adherents, and groups that remained loyal to the mission churches. In contrast, independent school initiatives in the rural Western Cape were characterised less by intra-community conflicts, than by bureaucratic engagement with the Education Department hierarchy, and the utilisation of supra-ethnic and supra-denominational political conduits such as the African Political Organisation.